On the Determination of the Speed of a Fast Solar Wind Stream Using Two Independent Measurements of the Interplanetary Magnetic Field - Martin Birch* (Annals of Mathematics and Physics, 2025)
Abstract The fast solar wind stream which resulted from the helio-meridional crossing of an equatorial coronal hole on June 29th and 30th 2005 passed the Wind and Advanced Composition Explorer (ACE) spacecraft during July 1st and 2nd. This fast stream caused a moderate magnetospheric storm following a weak (though clearly defined) sudden commencement at 14:12 UT on July 1st. During the event, the two spacecraft were both in the vicinity of the L1 libration point, though separated in the Sun-Earth direction by about 150000 km. An algebraic method is described whereby the speed of the particle flux can be determined using measurements of the interplanetary magnetic field at the two spacecraft.